INTEREST AS A LEGAL CATEGORY - A. Yu. Romanov (Финансы: теория и практика, 2017)
With the development of the market economy in Russia when the economic relations between subjects of entrepreneurial and other economic activities become more complicated the category of interest is becoming increasingly important and needs proper understanding and application. Identifying persons interested in making a transaction plays an important role in preventing the abuse of rights in the performance of legal actions as well as in the protection of the rights of company members. Despite its significance, the concept of interest is not fully developed in the scientific literature and not clarified by the courts in law enforcement procedures. Based on the studied information the paper suggests a broader understanding of the concept of interest exposing its key features. It points out the inaccuracy of the legislative language in regulations related to the concept of interest. The general definition of interest will be used in the future for further studies of business entities and their interests in business activities.